Depression literacy, mental health literacy, and their relationship with psychological status and quality of life in patients with type 2 diabetes mellitus - Jafari, Alireza; Moshki, Mahdi; Naddafi, Fatemehzahra; Ghelichi-Ghojogh, Mousa; Armanmehr, Vajihe; Kazemi, Kimia; Nejatian, Mahbobeh (Frontiers in Public Health, 2024)
Background This study was conducted to measure depression literacy (D-Lit) and mental health literacy (MHL) and to investigate their relationship with psychological status and quality of life among Iranian patients with type 2 diabetes mellitus (T2DM). Methods This cross-sectional study was conducted in 2021 among 400 patients with T2DM in Iran. Samples were selected using proportional stratified sampling. Data collection tools comprised a demographic questionnaire, measures of MHL and D-Lit, the diabetes quality of life (DQOL) scale, and the DASS-21. After confirming the normality of the data using the Kolmogorov-Smirnov test, parametric statistical tests (such as one-way ANOVA, independent samples t-test, and Chi-Square) were used to investigate the relationship between the variables using SPSS v22 software. The results of continuous quantitative data are reported in the form of means and standard deviations, and qualitative data are reported in the form of absolute and relative frequencies. Results In this study, 10.25% of the participants (n = 41) had severe depression, while 36.75% (n = 147) experienced severe anxiety. The mean (standard deviation) of MHL was 80.92 (9.16) from 130 points. Of the participants, only 1.7% (n = 7) did not answer any questions correctly on the D-lit scale, and only 5.8% (n = 23) were able to answer 15 questions or more correctly on the D-lit. MHL had a significant negative correlation with depression (r = −0.236), anxiety (r = −0.243), and stress (r = −0.155) (P < 0.001). There was a positive and significant correlation between MHL and D-Lit (r = 0.186) (P < 0.001). D-Lit had a significant negative correlation with depression (r = −0.192), anxiety (r = −0.238), and stress (r = −0.156) (P < 0.001). There was a positive and significant correlation between the ability to recognize disorders (r = 0.163), knowledge of self-treatment (r = 0.154), and DQOL (P < 0.001). Depression (r = −0.251), anxiety (r = −0.257), and stress (r = −0.203) had a significant negative correlation with DQOL (P < 0.001). Conclusion MHL and D-Lit levels were found to be inadequate in patients with T2DM. These low levels of MHL and D-Lit among patients with T2DM were associated with higher levels of anxiety, depression, and stress, as well as a lower quality of life. Therefore, designing and implementing preventive programs to improve the mental health of patients with T2DM can help prevent mental disorders and ultimately improve their quality of life.